Belgian Photographic Literature of the 19th Century. L'édition photographique belge au 19e siècle. : A Bibliography and Census. Bibliographie et recensement. - Joseph, Steven F., 1955- (Book collections on Project MUSE., 2016)
The development of photography from its roots in 19th century science gradually transformed book illustration and the dissemination of images. This reference work presents a first comprehensive overview of Belgian photographic literature of the 19th century, both illustrated books and scientific publications. It makes a major contribution to academic study in the field, with a corpus composed of 681 entries and, for each title, indicates locations of surviving copies in institutional collections in Belgium and elsewhere. An introductory essay plots the development of photographic publishing in Belgium, making full use of primary and secondary sources. An album of over eighty images draws on the rich iconography of early Belgian photographic literature, most reprinted here for the first time.